Vitamin D and its influence on human immune system - Arystanbay, A.A.; Zhumina, A.G.; Klunnaya, V.O. (Karagandy University of the name of acad. E.A. Buketov, 2022)
This review presents modern domestic and foreign studies of vitamin D levels effect on the human immune system. Numerous data are presented on the participation of vitamin D in the regulation of immune responses. In recent years, more and more attention has been paid to the problem of vitamin D deficiency in the body of patients with autoimmune diseases. The significance of vitamin D in immune regulation is confirmed by the results of many experimental studies, clinical and epidemiological observations that demonstrate the relationship between low levels of the vitamin D and increased susceptibility to various infections, as well as the activity of the infectious process of viral, bacterial, and fungal etiology. Vitamin D acts both directly and indirectly on immune cells such as B and T lymphocytes, dendritic cells and macrophages. The review focuses on the molecular mechanisms of activation of the immune response under the influence of vitamin D. Vitamin D exerts its effect through binding to the vitamin D receptor (VDR), which, in turn, together with other proteins, activates the transcription of protein genes involved in the body’s immune response. In this regard, it is necessary to draw the attention of researchers to the problem of the daily intake of vitamin D, especially in a pandemic situation.
Keywords: vitamin D; calcitriol; vitamin D receptor (VDR); innate immunity; adaptive immunity; autoimmune diseases